2006
DOI: 10.3168/jds.s0022-0302(06)72145-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of κ-Casein and Glycomacropeptide

Abstract: Glycomacropeptide (GMP), arising from the cleavage of kappa-casein by chymosin or pepsin, has been correlated with a wide variety of biological activities including immunosuppression capacity, inhibition of pathogen invasion, and induction of satiety. Due to the interest in exploiting such potential of GMP, we aimed at characterizing the immunogenic properties of GMP as an indication of its potential allergenicity. Immunogenicity of kappa-casein and GMP were investigated using 2 animal models based on differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…BGMP is produced both physiologically as a result of the digestion of κ‐casein in the stomach of neonates, and in the industry as a part of the whey produced during the cheese‐making process. As a nutrient, BGMP has an excellent safety record and in accordance with this, a recent study has described that it is not immunogenic, because it fails to induce T‐cell‐specific responses in mice, even when given in polymerised form, in contrast with the parent protein ( Mikkelsen et al ., 2006 ). As a consequence, this peptide is used in the production of infant formulas and due to its low content on aromatic amino acids, including phenylalanine, BGMP has been proposed to be useful in the making of products for individuals with phenylketonuria ( Nakai and Modler, 1999 ).…”
Section: Introductionmentioning
confidence: 72%
“…BGMP is produced both physiologically as a result of the digestion of κ‐casein in the stomach of neonates, and in the industry as a part of the whey produced during the cheese‐making process. As a nutrient, BGMP has an excellent safety record and in accordance with this, a recent study has described that it is not immunogenic, because it fails to induce T‐cell‐specific responses in mice, even when given in polymerised form, in contrast with the parent protein ( Mikkelsen et al ., 2006 ). As a consequence, this peptide is used in the production of infant formulas and due to its low content on aromatic amino acids, including phenylalanine, BGMP has been proposed to be useful in the making of products for individuals with phenylketonuria ( Nakai and Modler, 1999 ).…”
Section: Introductionmentioning
confidence: 72%
“…It is composed of 64 amino acids and contains varying units of N-acetylneuraminic (sialic) acid [4]. GMP has an excellent safety record and is not immunogenic [5]. Our previous studies have shown that GMP administration prevents allergen sensitization by reducing allergen-specific IgE titers and suppressing the proliferation of splenocytes and their production of interleukin (IL)-13 in sensitized animals, which reduces the severity of immediate cutaneous reaction and anaphylaxis induced by allergens [2].…”
Section: Introductionmentioning
confidence: 99%
“…mutans, sanguis and sobrinus to oral surfaces [4,7,[12][13][14]18], and it can modify the composition of plaque bacteria to control its acid production and in turn reduce the demineralisation of enamel and promote remineralisation [1,11,16]. The GMP is a source of N-acetyl-necromantic acid [17] and one study showed that dietary intake of GMP can increase the sialic acid content of saliva, with effects on its viscosity and protective function [20].…”
Section: Discussionmentioning
confidence: 99%